Selected Poems of Oscar Wilde - Wilde, Oscar, 1854-1900 (Salt Lake City, UT : Project Gutenberg, 1997)
"Selected Poems of Oscar Wilde" by Oscar Wilde is a collection of poetry created during the late 19th century, specifically the Victorian era. This compilation showcases Wilde's early lyrical works alongside his later, more mature pieces, reflecting on themes of love, beauty, and the human condition, culminating in the poignant "The Ballad of Reading Gaol," which critiques the justice system and explores the darkness of human emotion. The central poem, "The Ballad of Reading Gaol," serves as a narrative of remorse and reflection following the hanging of a man who killed the woman he loved. Wilde captures the complexities of guilt and the paradoxical nature of love through evocative language and dynamic imagery. Throughout the collection, Wilde's varied poems touch on different aspects of life, including nature, societal observations, and personal relationships, all interconnected by deep emotional currents. His use of vivid imagery and masterful verse invites readers to delve into the multifaceted experiences of human emotion, making the collection a compelling read for those interested in the depth of poetic artistry. (This is an automatically generated summary.)
The Ballad Of Reading Gaol -- Ave Imperatrix -- To My Wife - With A Copy Of My Poems -- Magdalen Walks -- Theocritus - A Villanelle -- Greece -- Portia -- Fabien Dei Franchi -- Phedre -- Sonnet On Hearing The Dies Irae Sung In The Sistine Chapel -- Ave Maria Gratia Plena -- Libertatis Sacra Fames -- Roses And Rue -- From 'The Garden Of Eros' -- The Harlot's House -- From 'The Burden Of Itys' -- Flower of Love.
Release date is 1997-12-01
Transcribed from the 1911 Methuen & Co. edition by David Price
Keywords: Poetry